Development and Field Evaluation of a Cabbage Harvester Unit - A Rezahosseini (Ferdowsi University of Mashhad, 2019)
Introduction Harvesting is one of the most difficult steps in cabbage production that is usually a costly intensive operation. Cabbage harvesting is often done by human labors in Iran. According to customs administration’s statistics, more than 54000 tons of cabbages have been exported from Iran in 2015. Development of cabbage harvesting industry is necessary, because of the large cultivation area and the short available harvesting time. So far, a few studies have been done on cabbage mechanized harvesting in Iran. The harvesting machines can reduce harvesting time to one-eighth in comparison with manual harvesting. Design and manufacturing of a harvester unit suitable for small cabbage farms in Iran were conducted in the present study. So the paper was aimed to investigate the performance of the harvester at the different forward velocities, attack angles and distances between the plants. Materials and Methods The proposed machine consists of two major units; the soil looser and the unit for pulling out, crops from the soil. In this machine, the blades loose the soil around the cabbage root after penetrating into the soil. Next, cabbage is pulled out from the soil by puller belts. The belts move contrary to forward speed direction and take crop to the backward of the machine. Mechanical and physical properties of the cabbages should be measured, because the harvester is directly in touch with the crop. These properties are firstly measured and then selection of the different components and machine manufacturing are done. Two narrow legs (tillage tools) equipped with one-side blade with attack angles of 20 and 25 degrees are used for losing the soil around the cabbage’s root. The force exerted on the blade was 5.47 kN. Finally, the harvesting force is estimated to be 164.8 N by using mechanical and physical properties of the cabbages. Experiments were conducted at the different forward velocity levels (2, 3.5 and 5 km h-1), attack angle of the blades at three levels (20, 25 and 30 degree) and the distance between the crops in two levels (40 and 60 cm) in a completely randomized design with three replications. Results and Discussion The analysis of variance of the effect of different parameters on the harvested crop numbers showed, that the effects of forward velocity and attack angle on the number of harvested crops were significant in 5 percent probability. But distance between crops did not have significant effect on the number of harvested crops. Also the effects of interaction between forward velocity and attack angle, forward velocity and distance between crops, attack angle and distance between crops on the number of harvested crops were significant in 5 percent probability. According to the results, the number of harvested crops and machine performance were decreased by increasing forward velocity. Moreover, designed machine had the best performance (80 percent) at an attack angle of 25 degrees and forward velocity of 2 km h-1. Conclusions The results showed, with increasing the forward speed from 2 to 5 km h-1 the harvest success decreased by 20 to 25 percent. Also, the harvesting quality did not change at the different distances between the plants. The highest machine capacity was more than 5300 plants per hour, which was observed at the forward velocity of 3.5 km h-1 and the attack angle of 25 degrees.